2013
DOI: 10.1111/fwb.12087
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in water level and the dynamics of zooplankton: a data‐driven modelling approach

Abstract: Summary 1. The zooplankton in Lake Kinneret (Israel) have undergone large fluctuations in recent decades, which have been linked to both biotic and abiotic processes. 2. By applying a data‐driven modelling approach to a long‐term database, and focusing on key abiotic (lake‐level change) and biotic (prey abundance) variables, we attempted to identify the possible factors impacting the lake’s zooplankton community. 3. We hypothesised that changes in the predatory zooplankton (adult cyclopoids) assemblage are dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The biotic processes in aquatic ecosystems could be acting separately or in tandem with abiotic forces in structuring planktonic communities at scales relevant to organisms, populations, and ecosystems (Gal et al 2013).…”
Section: Factors Controlling Zooplankton Communitymentioning
confidence: 99%
“…The biotic processes in aquatic ecosystems could be acting separately or in tandem with abiotic forces in structuring planktonic communities at scales relevant to organisms, populations, and ecosystems (Gal et al 2013).…”
Section: Factors Controlling Zooplankton Communitymentioning
confidence: 99%
“…Most zooplankters including Ceriodaphnia and T. prasinus, can only take particles smaller than 20 µm [23]. Those assemblage patterns are typical in reservoirs subjected to periodic water level variations [24,25,12,13]. According to these authors, the above mentioned species evidence adaptive advantages over larger Cladocera and Copepoda, not only on account of their feeding behaviour but also because they have shorter generation times and greater tolerance to large amounts of organic matter in the water.…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton responses to WLR in alpine reservoirs may be driven by bottom-up processes, but this remains unstudied because the few published studies focus on reservoirs in other climatic zones (e.g. Gal et al, 2013;Simoes et al, 2015). However, one study in a subarctic Newfoundland reservoir found that zooplankton biomass, which increased approximately 19-fold during 11 years after impoundment, was not correlated with increased nutrient or resource availability (i.e., bottomup processes) but instead with increased retention time and hence decreased washout of zooplankton (Campbell et al, 1998).…”
Section: Littoral Zonementioning
confidence: 99%